Hospital escape VR: desenvolvimento de um jogo sério para treinamento de evacuação hospitalar diante de um incêndio - Saint Martin, Victor Biagiotti (2022)
Imminent threatening situations can occur anywhere, including hospitals. In 2020, 51 cases of hospital fires were recorded in Brazil, approximately one case of fire per week. Hence, it is essential to ensure that healthcare workers are prepared to deal with this occurrence. To that end, hands-on evacuation training emerges as a critical activity to protect the Health Care Establishment (HCE) and their occupants. However, regular evacuation training has limitations: (1) it is not recommended to reproduce threatening or dangerous situations; (2) affects the typical routine of the establishment; (3) traditional training end up being performed a few times throughout the year; (4) only a small percentage of hospital staff participate; (5) the inclusion of features that can enhance the simulation realism — such as fire and smoke — is not allowed; and (6) knowledge retention and user engagement end up being harmed. In this context, VR emerges as an alternative to traditional evacuation training. Therefore, this work presents the research in progress of the design and development of a hospital evacuation training simulator in the face of a fire situation using the Design Science Research (DSR) method. Preliminary tests suggest that this prototype has the potential to be used as complementary training to traditional methods. However, it is essential, in future work, to improve gameplay and user interaction, improve fire propagation functionality, add Non-Player Character (NPC), and perform empirical comparisons.